REESE’S CONFLICTS IN TORREY PETER’S THE DETRANSITION, BABY - INDRIANI, LUTFIAH; Rahayu, Anik Cahyaning (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
This research discusses about Reese’s conflict in Torrey Peter’s The Detransition, Baby. This research aims to explain and describe Reese’s conflicts and the solution of her conflicts. This research use the novel, The Detransition, Baby as the source of the data. There are three kinds of the conflicts, physical, social, and psychological conflict. Because the topic of the study is about conflict, the intrinsic approach is used in this research. Focusing on significant sections that emphasize Reese's psychological, physical, and social difficulties, the novel Detransition, Baby itself serves as the main source of data. Textual analysis serves as the primary means of data collection and interpretation in this qualitative study. Max Weber's and Karl Marx's theories are used to analyze Reese’s conflicts and the solutions. The result of analysis shows that Reese experiences three kinds of conflicts, physical, social, and psychological. Reese suffers from severe and painful physical abuse at the hands of her boyfriend. However, she recovers emotionally from the incident and “ended up in the hospital” as a result of her self-destructive lifestyle. Reese experiences social isolation as a result of her mistakes and dating married men, which exacerbates her intense loneliness. Particularly because she feels shunned by cisgender society, she yearns for the position of mother. Her emotional battle to make room for herself is reflected in the tension between her desire to be a mother and the reality of role reversal in a polyamorous relationship. Keywords: conflict, physical, social, psychological, and struggle.